Screening interval recommendations following a normal colonoscopy in individuals with a familial risk of colorectal cancer - Plath, Jasper; Siebenhofer, Andrea; Guethlin, Corina; Blumenstein, Irina (Zeitschrift für Gastroenterologie, 2018)
Background In view of the increased risk of developing colorectal cancer (CRC) in individuals with affected first-degree relatives (FDRs), the German evidence-based S3 guideline recommends having the first screening colonoscopy early and then, following a normal examination, repeating it at least every 10 years. The aim of this analysis was to explore colonoscopy interval recommendations in clinical practice among individuals aged < 55 years with a familial risk of CRC.Methods We analyzed data from the FRIDA.Frankfurt study. Patients aged 40 – 54 years with at least 1 reported FDR with CRC (excluding suspected/known hereditary cancer syndromes) and a normal colonoscopy result (no findings) were included. Data on colonoscopist recommendations for intervals between subsequent colonoscopies were extracted from colonoscopy reports.Results Of 63 reports of normal colonoscopies, 20 (32 %) did not include a recommendation on when to undergo a further colonoscopy. Of 43 reports with recommendations, 40 (93 %) suggested an interval that was shorter than the recommended maximum interval in the guideline: 1 (2 %) was for a 3-year interval, 37 (86 %) were for 5-year intervals, and 2 (5 %) were for 8-year intervals.Conclusions Although the low number of cases limits generalizability, the results indicate that recommended intervals in clinical practice are considerably shorter than the recommended maximum interval in the guideline.
Keywords: colorectal neoplasms; familial risk; colonoscopy; surveillance; screening